2013
DOI: 10.1097/mnh.0b013e32835b3d54
|View full text |Cite
|
Sign up to set email alerts
|

Impaired pressure natriuresis is associated with interstitial inflammation in salt-sensitive hypertension

Abstract: Here, we review the mechanisms for the impairment in pressure natriuresis resulting from renal tubulointerstitial inflammation in reference to the normal physiologic mechanisms involved in this response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…The role played by oxidative stress in the medullary regions of the kidney, restricting nitric oxide availability and causing dysfunction of the pressure-natriuresis response, has been reviewed recently (8,30,36,48). Reduction of oxidative stress by hypoxiainducible factor 1␣ (23) can improve pressure natriuresis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role played by oxidative stress in the medullary regions of the kidney, restricting nitric oxide availability and causing dysfunction of the pressure-natriuresis response, has been reviewed recently (8,30,36,48). Reduction of oxidative stress by hypoxiainducible factor 1␣ (23) can improve pressure natriuresis.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure natriuresis refers to the increment in urinary sodium excretion (U Na V) that occurs when blood pressure rises and is the consequence of complex modifications in renal interstitial hydrostatic pressure, medullary blood flow, nitric oxide, reactive oxygen species, prostaglandins, and angiotensin II activity (8,30,36) that result in coordinated decreases in the surface distribution of apical sodium-hydrogen exchangers and basolateral Na-K ATPase activity (27). In SSHTN, the pressure-natriuresis relationship is less steep and shifted to the right so that higher bloodpressure levels are necessary to drive the natriuretic response required to maintain sodium balance (41).…”
mentioning
confidence: 99%
“…Details of the mechanisms by which renal interstitial inflammation may cause hypertension have been recently reviewed elsewhere. 15 Evidence showing the effects of renal interstitial inflammation also comes from experimental studies that investigated the impact of anti-inflammatory cytokines, such as IL-10, on blood pressure. Tinsley et al 16 showed that the administration of intraperitoneal IL-10 normalized blood pressure and improved endothelial dysfunction in pregnant deoxycorticosterone acetate/saline-treated rats.…”
Section: Experimental Data and Possible Pathways For Inflammation-indmentioning
confidence: 99%
“…Although angiotensinogen is the best understood example, reports indicate that, at least in rodents, ACE and tubular renin expression are also upregulated in many conditions associated with renal parenchymal injury. Another suggestion is that inflammatory cells express RAS components and therefore, in conditions of renal inflammation, can become a separate source of local angiotensin II [28, 29]. …”
Section: Introductionmentioning
confidence: 99%